(untitled) (Journal of the College of Education for Women, 2024)
This research focuses on the stages of development of Applied Climatology, where Greek scientists such as Hippocrates, Galen, and Ptolemy referred to the first ideas of this science, as they focus on the relationship between the changes of the seasons and the health, diseases, and physical composition of peoples. Then Arab scientists (such as Al-Yaqubi, Ibn El-Faqih, Al-Istakhri, Al-Maqdisi, Al-Biruni, Al-Azizi, Al-Maqrizi, Al-Sabti, Al-Ghazzi, IbnKhaldun, etc.) added many new ideas to Applied Climatology, represented in the relationship between climate, health, diseases, comfort, mood, and colors of people, and they linked the moderation of climate to the intelligence and strength of people, and their long lives. As for (contemporary) Western civilization, the beginnings of Applied Climatology science go back to the forties of the 20th century in the form of research and then expanded into books, as the first book in the English language on Applied Climatology dates back to 1963. This was followed by numerous publications within this specialty. There has also been a development in the Topics of this science. After the interest was focused on climate, human comfort, and urban design, the relationship developed into climate, politics, and satellites.